Severity Index of Neonatal Septicemia in Neonatal Intensive Care units Using Score for Neonatal Acute Physiology-II - Lamiaa Mohsen; Mourad Ramzy; Nermin Mohamed; Ahmed Youssef; Amira Hegazy; Dina Akmal (Mashhad University of Medical Sciences, 2021)
Background: This study aimed to evaluate the competence of the score for neonatal acute physiology (SNAP-II) as a tool to anticipate morbidity and mortality of neonates with early or late sepsis in neonatal intensive care units (NICUs). Methods: This prospective cohort study was conducted on all neonates of > 32 weeks with sepsis in tertiary NICUs at Cairo University Children Hospital and El Galaa Hospital For Armed Forces Officers Families, Cairo, Egypt, within May-October 2019. The eligible samples consisted of 100 neonates with septicemia who met inclusion and exclusion criteria and were enrolled. the score for neonatal acute physiology-II was calculated within 24 h of sepsis onset and followed up for 2 weeks for mortality and organ dysfunction (OD). The collected data were analyzed in SPSS software (version 25). Results: It was revealed thatSNAP-II was significantly higher in neonates who passed away, compared to the survived neonates (46±17 vs. 12±10, respectively; P<0.001). Moreover, SNAP-II was significantly higher in neonates who developed OD within 14 days of sepsis onset, compared to those without OD (37±17 vs. 9±7, respectively; P<0.001). The score for neonatal acute physiology-II at 14.5 was considered the best cut-off point in predicting OD with a sensitivity of 100%, positive predictive value of 70.4%, specificity of 81.2%, and negative predictive value of 100%. In addition, SNAP-II at 23.5 was considered the best cut-off point in predicting overall mortality with 100% sensitivity, 58.6% PPV, 85.5% specificity, and 100% NPV. Conclusion: Higher SNAP-II within 24 h of the early- or late-onset neonatal sepsis was a reliable predictor of OD and death.